Analisis Komparatif Mazhab Maliki dan Mazhab Hambali Terhadap Status Hukum Wakaf Mu’aqqat: A Comparative Analysis of The Maliki and Hambali Mazhab on the Legal Status of Mu’aqqat Waqf (AL-FIKRAH: Jurnal Kajian Islam, 2025)
The background of this research lies in the ongoing debate regarding the validity of temporary (mu’aqqat) waqf in Islamic jurisprudence. The Maliki school permits it, while the Hanbali school rejects it. This difference forms the foundation of a comparative study to understand its legal status. This research aims to compare the perspectives of the Maliki and Hanbali schools on the legal status of temporary waqf. The study employs a qualitative descriptive approach using library research as the primary method for data collection. It adopts both normative and comparative methods, with data analyzed qualitatively through a deductive approach. The findings indicate that the Maliki school allows temporary waqf as long as the time limitation is explicitly stated in the contract. The requirement for waqf to be perpetual (mu‘abbad) is not seen as absolute, provided that the benefits of the waqf property can still be legitimately distributed to the rightful beneficiaries. On the other hand, the Hanbali school maintains that waqf must be permanent (mu‘abbad), based on the Prophet Muhammad’s (peace be upon him) statement prohibiting the sale, inheritance, or gifting of waqf property. As an implication, this study is expected to contribute to the development of contemporary Islamic legal studies, particularly in the field of mu‘amalah (social transactions), and to demonstrate the flexibility of waqf law in responding to the dynamics of the modern era.